2013
DOI: 10.4103/0974-7761.136044
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of Dental Students′ knowledge of radiation protection and practice

Abstract: Objective: To assess dental students' knowledge of dental radiation protection and practice as well as correlating their knowledge to practice on dental radiography. Materials and Methods: A cross-sectional questionnaire based study on radiation protection among dental students. Correct responses to the questions were allocated 1 mark while wrong response received no mark. Statistical analysis was performed using SPSS version 17 (Chicago, IL.). Pearson's coeffi cient correlation analysis was performed to estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
0
8
0
5
Order By: Relevance
“…The BDS students should have proper knowledge of this concept so that they can provide the maximum benefit to the patient along with taking care of the health of their staff and other individuals sitting in their dental set up. 8 After the student has completed his/her graduation, he/she is expected to take the dental radiographs with great precision, minimum attempts showing fine details following all the concepts of image formation along with protection of himself, his staff and patients from radiation hazards as far as possible. These may include wearing of lead apron and thyroid collar, following position distance rule and all the safety requirements of x-ray room.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BDS students should have proper knowledge of this concept so that they can provide the maximum benefit to the patient along with taking care of the health of their staff and other individuals sitting in their dental set up. 8 After the student has completed his/her graduation, he/she is expected to take the dental radiographs with great precision, minimum attempts showing fine details following all the concepts of image formation along with protection of himself, his staff and patients from radiation hazards as far as possible. These may include wearing of lead apron and thyroid collar, following position distance rule and all the safety requirements of x-ray room.…”
Section: Discussionmentioning
confidence: 99%
“…9 The concept of ALARA is very important when radiology comes into picture which suggests that radiation should be as low which can be achieved within practical limits. 8 There should be a balance between the side effects and the benefits produced by a single radiograph. Speaking in detail that every radiograph should only be done if it increases the ability of a dentist to diagnose a condition and treat it by comparing them with the side effects it is going to have on the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Usefulness of collimators and filters in dental radiography was known by 89% of the participants. Conversely, Arnout reported only 44% [4] , Arnout and Jafar reported an acceptable 73% [6] , Enabulele and Igbinedion reported 50% [11] , whereas Prabhat et al [1] and Rahal et al [10] reported high results (90% and 83.3%, respectively). The knowledge of deterministic and stochastic effects and ALARA principle were evident in 86% of the participants, which is similar to Shah et al (98.6%) [9] and Prabhat et al (84%) [1] , whereas Arnout and Arnout and Jafar reported only 33% and 40%, respectively [4,6] .…”
Section: Discussionmentioning
confidence: 99%
“…[27] In contrast, in other surveys, radiologic technologists had better safety knowledge than practice. [1328] Shah et al .…”
Section: Discussionmentioning
confidence: 99%
“…In line with our study, low level of RP-knowledge and a little better practice among dental students were indicated in the study of Enabulele and Igbinedion. [ 27 ] In contrast, in other surveys, radiologic technologists had better safety knowledge than practice. [ 13 28 ] Shah et al .…”
Section: Discussionmentioning
confidence: 99%